Influência do defeito esfincteriano na resposta ao biofeedback em pacientes com incontinência fecal - Kaiser Junior, Roberto Luiz (2014)
Introduction: Fecal incontinence is defined as the recurrent uncontrolled passage of stool for at least 1 month's duration in an individual with a age of at least 4 years. If conservative management fails or surgical intervention is not indicated, biofeedback therapy may be considered. Objective: To assess the influence of sphincter defect in the response to biofeedback in patients with fecal incontinence, considering manometry, electromyography and incontinence score. Patients and Methods: A total of 242 patients with fecal incontinence (mean age: 70.5 ± 14.0 years; range 10 to 100 years) underwent biofeedback were studied. Patients were evaluated using anorectal physiology tests and Cleveland Clinic Florida Fecal Incontinence score (CCF-FI) before and after biofeedback. Manometry including resting and squeeze pressures was performed before biofeedback. Electromyographic activity at resting and squeeze before and after biofeedback was recorded. Defects in the internal and external anal sphincters were detected by endoanal ultrasound. Results of physiologic tests and CCF-FI score before and after biofeedback were compared with one-sample t test (or Wilcoxon test as appropriate). A two independent sample t test (or Kruskal-Wallis test as appropriate) was used for comparison between groups with and without defect. Results: Among the 242 patients with fecal incontinence, 143(59.1%) underwent ultrasonography whose anatomical alterations in the sphincter were detected in 43(30.1%) individuals. Before biofeedback, there was no significant difference between resting and squeeze pressures in patients with and without sphincter defect. Electromyography before and after biofeedback in patients with and without sphincter defect showed no significant difference. Of the 66 individuals who responded to CCF-FI score before biofeedback, there was decrease in 45(68.2%), no alteration in 18(27.3%) and increase in 3(4.5%). Comparison between score before and after biofeedback of individuals with and without sphincter defect revealed no significant difference. After mean time of 6.1 years, of the 54 patients who responded to CCF-FI, 31(57.4%) reduced the score, 4(7.4%) remained unaltered and 19(35.2%) increased. Before and after this mean time, fecal incontinence score of patients with and without sphincter defect demonstrated a significant difference (P = 0.021) and the score in patients with defect was higher than those with no defect. Conclusions: Sphincter defect did not influenced in the response to biofeedback in patients with fecal incontinence. Manometry before biofeedback revealed that individuals with and without sphincter defect showed sufficient muscle conditions for indication of this therapy. Increase of electromyographic activity at squeeze after biofeedback indicated a satisfactory response of the sphincter musculature, independent of the presence or absence of defect. Regarding fecal incontinence score, there was a clinical improvement in most patients both immediately after biofeedback as after mean time of 6.1 years. Presence or absence of sphincter defect did not alter significantly the clinical outcome following biofeedback, however after 6.1 years better results were obtained in those with no defect.